A Performance-Driven Hybrid Framework for Data Mining Using Advanced Deep Learning Ensembles - Sarita Naruka,; Arvind Kumar Sharma,; Amit Sharma, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Data mining is very important for getting useful information out of big, complicated databases. But the many problems that come up because of data complexity, scalability, and algorithmic restrictions mean that new ways of doing things are needed to get the best results. This study looks at the creation of a hybrid framework that combines several machine learning techniques to make data mining applications more accurate, reliable, and efficient. The first part of the paper compares well-known machine learning algorithms and points out their pros and cons. The hybrid framework solves important problems including overfitting, parameter sensitivity, and data imbalance by using the best parts of various techniques together. The suggested solution uses ensemble methods and mathematical formulas to make sure it can work with a wide range of datasets and be scaled up or down as needed. Experimental evaluation demonstrates that the hybrid model consistently outperforms standalone algorithms in metrics such as accuracy, precision, and execution time. Applications in domains like healthcare, finance, and energy management underscore the practical relevance of the framework. This study adds to the increasing body of knowledge in machine learning by suggesting a systematic way to hybridization. This provides a strong answer for real-world data mining applications. The results show how hybrid frameworks might change the way data-driven decisions are made, opening the door to further progress in the subject.
Keywords: Linear regression; Logistic regression; Decision tree; SVM; Naive Bayes; KNN; Random Forest